Geographical Differences in Autoantibodies and Anti-infectious Agents Antibodies Among Healthy Adults (2011)
Much is known about the geoepidemiology of defined autoimmune diseases (AD); however, there is currently limited data regarding the prevalence of autoantibodies among healthy populations of different geographical areas. The aim of this study was to evaluate a large profile of autoantibodies in healthy adults from distinct global regions as well as the prevalence of anti-infectious agents antibodies in those regions. Sera samples from 557 healthy donors were obtained at six centers located in different countries (i.e., Italy, Netherlands, Israel, Mexico, Columbia, Papua New Guinea (Kitavans)). Sera were tested for the presence of antinuclear antibodies (ANA) and autoantibodies associated with thrombophilia, vasculitis, and gastrointestinal (GI) disease. Sera samples were also screened for antibodies against infectious agents (i.e., EBV, CMV, HBV, Helicobacter pylori, Treponema pallidum, and Toxoplasma gondii). Tests were performed using the BioPlex 2200 or ELISA kits (Bio-Rad Laboratories, USA). We found a significant gradient of ANA positivity among the groups: 45% of Columbians, 38% of Kitavans, 26% of Mexicans, 12% of Italians, 12% of Dutch, and 11% of Israelis were ANA positive. Geographical differences were also observed regarding the prevalence of specific autoantibodies, namely ANA: anti-dsDNA, chromatin, SmRNP, Ro/SSA, La/SSB, Scl70; GI associated: antigliadin; and thrombophilia-associated: anti-?2GP1 and prothrombin. Additionally, significant differences were observed regarding serological markers of all infectious agents screened. The observed variance between healthy ethno-geographical distinct populations in prevalence of autoantibodies may represent different genetic or environmental (e.g., prior exposure to infection) influences. Thus may illuminate possible causes of geoepidemiological differences in AD.